2005
DOI: 10.1021/ac050404f
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Immobilized Metal Affinity-Based IMAC/C18 Tip Enrichment of Phosphopeptides for Protein Phosphorylation Analysis

Abstract: We have developed a simple, highly specific enrichment procedure for phosphopeptides, by increasing the specificity of an immobilized metal affinity column (IMAC) without using any chemical reaction. The method employs a biphasic IMAC-C18 tip, in which IMAC beads are packed on an Empore C18 disk in a 200-microL pipet tip. Phosphopeptides are separated from non-phosphopeptides on the IMAC in an optimized solvent without any chemical reaction, then desorbed from the IMAC using a phosphate buffer, reconcentrated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
182
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(188 citation statements)
references
References 66 publications
4
182
0
2
Order By: Relevance
“…Second, the acetonitrile/water solvent system for the TSKgel Amide-80 column contains 0.1% TFA, and the majority of phosphopeptides elute between 70 and 50% acetonitrile. Oda and co-workers (22) have shown that the best recovery and greatest selectivity for IMAC occurs when the loading buffer contains between 0.1 and 1.0% TFA and between 45 and 65% acetonitrile. Thus FIG.…”
Section: Resultsmentioning
confidence: 98%
“…Second, the acetonitrile/water solvent system for the TSKgel Amide-80 column contains 0.1% TFA, and the majority of phosphopeptides elute between 70 and 50% acetonitrile. Oda and co-workers (22) have shown that the best recovery and greatest selectivity for IMAC occurs when the loading buffer contains between 0.1 and 1.0% TFA and between 45 and 65% acetonitrile. Thus FIG.…”
Section: Resultsmentioning
confidence: 98%
“…Phosphopeptides were purified from approximately 1 mg each sample. The use of IMAC/C18 columns is described in the literature (Kokubu et al, 2005;Ficarro et al, 2009;Mertins et al, 2013). Fe 31 -IMAC resin was created by taking Ni-NTA Superflow agarose resin (Qiagen, Germantown, MD) and stripping out Ni by incubating with 500 mM EDTA, pH 8 (1:1 v/v), for 5 minutes, and repeating.…”
Section: Methodsmentioning
confidence: 99%
“…By decrease in the pH of the IMAC loading conditions further (below pH 1.9), more acidic peptides will become neutralized while phosphopeptides will retain their negative charge and their binding affinity toward the IMAC resin. Kokubu and co-workers showed that 0.1% TFA, 50% ACN as IMAC loading buffer reduced the level of nonspecific binding and improved the specificity of the method toward phosphopeptides [56]. Yet another approach to improve the performance of IMAC is to reduce the complexity of the peptide samples by prefractionation using methods such as IEF [57][58][59][60], Ion Exchange Chromatography [41,43,46,61] or hydrophilic interaction chromatography (HILIC) [62] prior to IMAC purification.…”
Section: Immobilized Metal Ion Affinity Chromatographymentioning
confidence: 99%